Limiting fear and anger responses to anger expressions. Issue 4 (19th December 2019) - Rees, Laura; Friedman, Ray; Olekalns, Mara; Lachowicz, Mark
Abstract : Purpose: The purpose of this study is to test how individuals' emotion reactions (fear vs anger) to expressed anger influence their intended conflict management styles. It investigates two interventions for managing their reactions: hot vs cold processing and enhancing conflict self-efficacy. Design/methodology/approach: Hypotheses were tested in two experiments using an online simulation. After receiving an angry or a neutral message from a coworker, participants either completed a cognitive processing task (E1) or a conflict self-efficacy task (E2), and then self-reported their emotions, behavioral activation/inhibition and intended conflict management styles. Findings: Fear is associated with enhanced behavioral inhibition, which results in greater intentions to avoid and oblige and lower intentions to dominate. Anger is associated with enhanced behavioral activation, which results in greater intentions to integrate and dominate, as well as lower intentions to avoid and oblige. Cold (vs hot) processing does not reduce fear or reciprocal anger but increasing individuals' conflict self-efficacy does. Research limitations/implications: The studies measured intended reactions rather than behavior. The hot/cold manipulation effect was small, potentially limiting its ability to diminish emotional responses. Practical implications: These results suggest that increasing employees' conflict self-efficacy can be an effective intervention for helping them manage the natural fear and reciprocal anger responses when confronted by others expressing anger. Originality/value: Enhancing self-efficacy beliefs is more effective than cold processing (stepping back) for managing others' anger expressions. By reducing fear, enhanced self-efficacy diminishes unproductive responses (avoiding, obliging) to a conflict.